SAT0507 EVALUATION OF THE NEW CLASSIFICATION CRITERIA FOR PFAPA SYNDROME. (June 2019) - Crimi, Fabio; Mejbri, Manel; Hentgen, Véronique; Dingulu, Glory; Koné-Paut, Isabelle; Georgin-Lavialle, Sophie; Pillet, Pascal; Hofer, Michael; ,
Abstract : Background: Modified Marshall criteria used for PFAPA syndrome have never been validated and are little used by the experts because the symptoms of monogenic fevers often overlap with PFAPA ones. A new set of classification criteria based on an international survey and a consensus conference in Genoa was developed in 2018. Objectives: Evaluate the performance of the new criteria in a real-life setting Methods: This is a multicentric, prospective and descriptive cohort study, through the recurrent fever module of the JIRcohorte platform. 417 patients diagnosed with PFAPA (187), monogenic fever syndromes (167) or unclassified recurrent fever syndrome (UPF=63) from Swiss and French centers were enrolled in the study. The new classification criteria were applied to this cohort and we calculated their performance. We then analyzed which of the criteria performed the less well. Results: One hundred fourteen from 187 (61%) PFAPA patients met the new criteria, as well as 20/230 non-PFAPA patients (FMF: 3, MKD: 4, UPF: 13); 73 PFAPA patients did not meet the criteria. We calculated a specificity of 91.3% and a sensitivity of 60.9%. The least satisfied criterion among PFAPA patients not meeting the criteria was "absence of skin rash". By removing this criterion, the sensitivity improved (81.2%), but the specificity decreased slightly to 86%. Conclusion: Genoa 2017 classification criteria for PFAPA syndrome showed a good specificity but an insufficient sensitivity. Excluding the less satisfied criterion, the set reaches a sensitivity and specificity around 80% which could be a fair compromise for PFAPA classification criteria. Our study highlights the difficulty in establishing classification criteria due to the lack of gold standard for PFAPA diagnosis. References: [1] Vanoni F, Federici S, Antón J, Barron K, Brogan P, De Benedetti F, Dedeoglu F, Demirkaya E, Hentgen V, Kallinich T, Laxer R, Russo R, Toplak N, Uziel Y, Martini A, Ruperto N, Gattorno M, Hofer M. An international Delphi survey for the definition of the variables for the development of new classification criteria for Periodic Fever Aphthous stomatitis Pharyngitis Cervical Adenitis (PFAPA). Pediatr Rheumatol Online J. 2018, 16(1):27. Disclosure of Interests: Fabio Crimi: None declared, Manel Mejbri: None declared, Véronique Hentgen Consultant for: SOBI, Novartis, Abbvie, Speakers bureau: Novartis, Glory Dingulu: None declared, Isabelle Koné-Paut Grant/research support from: SOBI has supported drug product (anakinra) for the presented study, Consultant for: SOBI, Novartis, Pfizer, Abbvie, UCB, CHUGAI, ROCHE, Sophie Georgin-Lavialle Consultant for: novartis, sobi, Speakers bureau: novartis, sobi, Pascal Pillet: None declared, michael hofer Grant/research support from: novartis, SOBI, Consultant for: Novartis, SOBI